Clinical and genetic analysis in males with 46, XX disorders of sex development: A reproductive centre experience of 144 cases. (8th January 2019) - Chen, Tong; Tian, Linlin; Wu, Fei; Xuan, Xujun; Ma, Gang; Tang, Rong; Lu, Jiaju
Abstract: To explore the clinical features and assisted reproductive technology (ART) outcomes of 46, XX disorders of sex development (DSD) males, 144 males with 46, XX DSD were recruited in this retrospective study. The baseline information, clinical characteristics and ART outcomes of the participants were collected and analysed. The mean age was 29.06 ± 4.50 years. The mean volumes (95% CI) of left and right testicles were 2.16 (1.82–2.49) ml and 2.16 (1.83–2.49) ml, respectively. Cryptorchidism and/or hypospadias appeared in 19 patients (13.19%). Elevated levels of follicle‐stimulating hormone (FSH) were found in 136 patients (95.10%) and increased luteinising hormone (LH) values were detected in 125 patients (92.59%). Eighty subjects (62.99%) had low testosterone values. Among 86 patients with status of sex‐determining region Y ( SRY )—gene and azoospermia factor (AZF) region available, fifteen (17.44%) patients were SRY ‐negative and AZF region was absent in every patient without exception. Additionally, fertility achieved in 87 patients through ART using donor spermatozoa. In conclusion, hypergonadotropic hypogonadism appeared as the main presentation of 46, XX DSD males regardless of the SRY status. The available fertility option proved to achieve live birth was limited to ART using donor spermatozoa.